2019
DOI: 10.1080/14756366.2019.1624541
|View full text |Cite
|
Sign up to set email alerts
|

Identification of phenazine analogue as a novel scaffold for thioredoxin reductase I inhibitors against Hep G2 cancer cell lines

Abstract: Even though phenazines have been extensively reported as anticancer molecules, the molecular target of these compounds is severely lagging behind. Our study consequently focuses on the anticancer target of a phenazine analogue ( CPUL1 ) for its potently antitumor activities in initial stage. Along with redox status courses of Hep G2 cells, thioredoxin reductase I (TrxR1) was speculated as anticancer target of CPUL1 . By virtue of zymologic, immunological and molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Recently, based on the strategy of molecular hybridization, our group successfully screened out pyran‐phenazine hybrid molecules CPUL129 and CPUL149 ( Figure 1) from the phenazine library established by us before [11–18] . These compounds could accumulate and sequester iron in lysosomes through interacting with iron and regulating the expression of proteins (IRP2, TfR1, ferritin) engaged in iron transport and strorage, eventually specifically inhibit the stemness of breast cancer cells through triggering ferroptosis [19] …”
Section: Introductionmentioning
confidence: 99%
“…Recently, based on the strategy of molecular hybridization, our group successfully screened out pyran‐phenazine hybrid molecules CPUL129 and CPUL149 ( Figure 1) from the phenazine library established by us before [11–18] . These compounds could accumulate and sequester iron in lysosomes through interacting with iron and regulating the expression of proteins (IRP2, TfR1, ferritin) engaged in iron transport and strorage, eventually specifically inhibit the stemness of breast cancer cells through triggering ferroptosis [19] …”
Section: Introductionmentioning
confidence: 99%
“…In previous work, we successfully screened out a novel TrxR inhibitor CPUL1 from the compound library established by our group before, but poor water solubility greatly limits its further antitumor application. In recent years, carrier-free nanomedicine completely composed of active pharmaceuticals has attracted a lot of attention. We recently used carrier-free, mitochondria-targeting strategy to prepare self-assembled nanoaggregates (CPUL1-TPP NAs) composed of CPUL1 and a triphenylphosphine (TPP) derivative through electrostatic and π–π stacking interactions, with the aim to enhance antitumor efficacy of insoluble CPUL1 on HUH7 hepatoma cells as well as meliorate drug solubility and enhance intracellular drug accumulation in cytoplasm.…”
Section: Introductionmentioning
confidence: 99%
“…As one of the synthetic phenazines, the active substance of pyrano [3,2-a]phenazine, also called CPUL1 (Figure S1B), has shown high inhibitory effects on various tumor cells, including gastric, liver, and breast cancers [5][6][7]. Furthermore, CPUL1 displayed the best antiproliferative activity against HepG2 cancer cells without obvious cytotoxicity against human normal liver epithelial L02 cells, suggesting a better safety potential [8,9]. Further pharmacological mechanistic studies revealed that CPUL1 inhibited topoisomerase I/II, promoted GSH depletion, and induced apoptosis through a mitochondrial-dependent pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Further pharmacological mechanistic studies revealed that CPUL1 inhibited topoisomerase I/II, promoted GSH depletion, and induced apoptosis through a mitochondrial-dependent pathway. Moreover, CPUL1 acted as a thioredoxin reductase 1 (TrxR1) inhibitor and activated apoptosis through the ROS-Trx-ASK1-p38 pathway [7][8][9]. Thus, CPUL1 was regarded as a promising anticancer candidate compound.…”
Section: Introductionmentioning
confidence: 99%